EFEKTIVITAS PENGEMBANGAN WISATA KEBERLANJUTAN DESA SUMBERGONDO BERBASIS COMMUNITY BASSED TOURISM - Kholifatul , Nurul; Tsurrayya, Nabila; Khosiba, Nahdya; Rahman, Haqqi Sabil; Firmansah, Alfian Dwi; Hermawan, Andi Agus; Moeljanto, Wahyu Nurmohammad; Wicaksono, Zulfikar Bisma; Romadhon, M. Yusuf (Nindikayla Institute, 2025)
The socialization of business innovation in Sumbergondo Tourism Village, Batu, aims to empower the community in developing sustainable tourism potential. Through a participatory approach, this socialization involves the local community in understanding the importance of business innovation as a strategy to increase village competitiveness as a tourist destination. This activity includes business management training, local product marketing, and sustainable management of natural and cultural resources. By actively involving the community, it is hoped that they can implement innovative ideas that not only increase economic income, but also maintain the sustainability of the local environment and culture. The results of this socialization show an increase in community knowledge and skills in managing tourism businesses, as well as the formation of a network of cooperation between business actors. Thus, this activity contributes to the development of sustainable tourism in Sumbergondo Village and improves the welfare of the local community.